A metal–organic framework based inner ear delivery system for the treatment of noise-induced hearing loss. Issue 30 (29th July 2020) - Xu, Xiaoxiang; Lin, Kun; Wang, Yanzhi; Xu, Kai; Sun, Yu; Yang, Xiuping; Yang, Minlan; He, Zuhong; Zhang, Ya; Zheng, Haoquan; Chen, Xiong
Abstract : A novel zeolitic imidazolate framework (ZIF)-based system for methylprednisolone (MP) delivery in the inner ear was developed and exhibited good protection of mice from noise and low side effects. Abstract : Noise-induced hearing loss (NIHL) is associated with both acute and chronic noise exposure. The application of steroid hormones is the first-line treatment for NIHL. However, a high dose of steroid hormone in the body is necessary to maintain its efficacy and causes side effects, such as headache and osteoporosis. In this work, we prepared a zeolitic imidazolate framework (ZIF)-based system for steroid hormone delivery in the inner ear. Methylprednisolone (MP), a typical steroid hormone, was encapsulated into ZIF-90 nanoparticles (NPs) using one-pot synthesis method. The obtained MP@ZIF-90 NPs are negatively charged and 120 nm in size and showed good biocompatibility and stability at a pH value of 7.4. After intraperitoneal injection, ZIF-90 could efficiently protect drugs during peripheral blood circulation, enter the inner ear via the blood labyrinthine barrier (BLB) and slowly release the drugs. Auditory brainstem response (ABR) tests indicated that MP@ZIF-90 exhibits better protection of mice from noise than those using the free MP and ZIF-8 with encapsulated MP (MP@ZIF-8). More importantly, MP@ZIF-90 showed no defects to the inner ear after being treated for noise and low nephrotoxicity during therapy, which demonstrates the biocompatibility of this material. We believe the ZIF-90 based delivery system is an efficient strategy for inner ear therapy of NIHL.